National Plan for Training Personnel To Serve Children with Blindness and Low Vision Christine Mason and Roseanna Davidson. - Mason, Christine (Distributed by ERIC Clearinghouse, 2000)
This document presents a national strategic plan for preparing capable and qualified personnel to educate students who have visual impairments. The plan focuses on three main goals: (1) to increase the number and diversity of qualified personnel to serve students with visual impairments; (2) to increase the number and diversity of qualified leadership personnel in the education of children with visual impairments; and (3) to increase the number and diversity of high-quality applicants to and graduates from personnel preparation programs serving all areas of education of students with visual impairments. Section 1 provides background information on the project. Section 2 discusses the needs assessment designed to assist the strategic plan, estimates of children to be served, and recommendations for more reasonable caseloads. Section 3 presents the most critical goals, objectives, and strategies needed to address the shortage of direct service personnel who serve students with visual impairments. It includes a description of the planning process and the recommended implementation plan. Tables provide funding requirements, potential partners, and performance indicators for each implementation strategy. The final section discusses the anticipated impact of implementation of the plan and its costs. Appendices include supporting research and data. (Contains 25 references.) (CR)